Vendors' team performance in software outsourcing projects: From the perspective of transactive memory systems behavioral characteristics. Issue 3 (29th July 2014) - Qu, Gang; Shen, Lishan; Bao, Xiaona
Abstract : Purpose: – The purpose of this paper is to study how the software outsourcing teams, namely, vendors, transfer effective knowledge to enhance team performance; it reports on a study of transactive memory system (TMS) theory and makes deep analyses and discussions about the influence of the cooperative behaviors of TMS on software outsourcing team's performance under the framework of three behavioral characteristics dimensions – specialization, credibility and coordination. Design/methodology/approach: – This paper is an empirical study based on investigation interviews to 28 software outsourcing teams and data of questionnaire surveys on 124 software outsourcing teams; structural equation model is used to test the data we collected. Findings: – This paper finds that both credibility and coordination have a significantly positive impact on knowledge transfer and project success, whereas specialization has a significant negative impact on project success. The results of data analysis show that TMS is an effective coordination mechanism. Originality/value: – The conclusion of the study can help us understand the coordination mechanism of knowledge transfer in software outsourcing team and provide theoretical support and paradigm reference for vendors in China to accumulate knowledge and improve the success rate of projects in the context of software project development.